Analisis Tingkat Keaktifan Pengelolaan Hutan Desa Labbo - Andi Batari; Yusran Yusran; Muhammad Alif K Sahide (Jurnal Hutan dan Masyarakat, 2017)
The purpose of the research to analysis forest management level activity at Desa Labbo intens to Production, Distribution and Local Institution with the comparison of achievement program in the establishment formal document RKHD (Rencana Kerja Hutan Desa),RTHD (Rencana Tahunan Hutan Desa), village regulation 02 of 2010 and guideline of 01/BMDS-GT/LB/KTB/II/2010 based on the reality, and to determine forest management Desa Labbo Categorized by active management or hollow management to known stakeholder/actor get benefit or harmed by the hollow management system. Research will be held on Januari 2017 at Desa Labbo Kecamatan Tompobolu,Kabupaten Bantaeng of South Sulawesi. This Research use the snowball sampling system(triangulasy system). Snowball sampling like as snowball was rolling in the end was bigger, like as collect information the research. Interview at the respondent to get accuracy information and verify to get validity data. Research Object are Formal Document Establishment of Implementation Planning in the Document with comparison the real condition. Result research showing forest management system Desa Labbo Categorized active management will be realization 25,19%, not realization 41,20%, that counting can not to compare with high and low, important or not with the unsure (production,distribution,institution), because the unsure of research will be get the same research. About the actor will be get benefit at the hollow management status at forest village Labbo is head of village but the Actor will be get Hermed by active management system is balang institute.